Salário mínimo nacional, alimentação básica e segurança alimentar: um estudo para o Brasil - Batista, Alberth Martins (2019)
The Minimum Wage was instituted in Brazil in 1936, in accordance with Law Nº 185 of 1936 and Decree Law Nº 399 of April 1938. According to the 1988 Constitution the minimum wage must be able to meet the basic vital needs of the worker. and his family, which concern food, clothing, housing, hygiene, and transportation. Regarding food, the Intersindical Department of Statistics and Socioeconomic Studies (DIEESE) established, based on Decree Law Nº 399, a list of foods, with their respective quantities, called the basic food basket. This would be enough for the monthly livelihood and well-being of an adult worker, containing balanced amounts of protein, calories, iron, calcium and phosphorus. DIEESE conducts the “Basic Food Basket Cost Survey” monthly in 18 Brazilian state capitals. Also, regarding food, the National Household Sample Survey (PNAD) provides data on food security for 2004, 2009 and 2013. In view of the above, the present study sought to verify whether the national minimum wage has been able to provide family basic food, as well as food security. The purpose is therefore to verify not their ability to meet all the constitutionally referred vital needs, but only those of food for a medium size family. In general, the work emphasized the importance of the theme of study, especially in Brazil, where the portion of the population living on the minimum wage is significant. Considering the proposed, the research showed, on the one hand, that the value of the national minimum wage does not guarantee the basic food for a medium-sized family and, on the other, that there is a direct relationship between household income and security.